2016
DOI: 10.1186/s12903-016-0161-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the autogenous bone block transfer for dental implant placement: Symphysal or ramus harvesting?

Abstract: BackgroundThe absence of sufficient bone volume is the most relevant problem in implant dentistry. Grafting from exogenous sources may provide a limited gain but exhibits poor performance in large bone defects. Autogenous bone block transfer (ABBT) from the mandibular symphysis and ramus has been used with varying rates of success. The aim of this study was to compare the efficacy of symphysal and ramus ABBT for the restoration of lost horizontal alveolar bone volume in the anterior maxilla. Implants placed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 21 publications
1
46
0
7
Order By: Relevance
“…There is a great discrepancy in the literature about the extent of horizontal bone gain after bone augmentation with RBG and GBR. Previous studies involving two-stage approaches have reported a mean horizontal bone gain ranging from 4 to 6 mm after RBG [3, 4, 7, 10, 24, 25], while the mean horizontal bone gain in GBR approaches has been reported to range from 1.37 to 6 mm [18, 19, 21, 26, 27]. Our results for both groups are in agreement with those of previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…There is a great discrepancy in the literature about the extent of horizontal bone gain after bone augmentation with RBG and GBR. Previous studies involving two-stage approaches have reported a mean horizontal bone gain ranging from 4 to 6 mm after RBG [3, 4, 7, 10, 24, 25], while the mean horizontal bone gain in GBR approaches has been reported to range from 1.37 to 6 mm [18, 19, 21, 26, 27]. Our results for both groups are in agreement with those of previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…Out of the 23 studies (Table 1), there were 11 randomised controlled clinical trials [21-24, 26, 29-32, 36, 37, 39], one prospective cohort study [34,40], three retrospective cohort studies [18,20,33], and eight case series [16,17,19,25,27,28,35,38,[41][42][43], of which two research groups independently published two follow-up papers on the same study cohort [21,22,27,28], and they have been collectively grouped under one study name for this analysis. The follow-up period after ridge augmentation or implant placement was reported in all studies except two [16,35], and it ranged from 3.1 months to 10 years.…”
Section: Study Design and Characteristicsmentioning
confidence: 99%
“…The placement of dental implants in the distal edentulous maxillary area is often a problem in case of the severely resorbed maxilla and presents a complex challenge to the oral and maxillofacial surgeon [ 2 , 3 , 4 , 5 ]. Inadequate bone height in the lateral part of the maxilla forms a contra-indication for implant surgery; due to the significant resorption in the posterior maxilla following tooth extraction and the pneumatization of the maxillary sinus, there is not enough bone volume to ensure primary stability of dental implants [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%